Assessment of Weedicides and Nitrogen on Range Grassland Productivity - Pandey, R. K.; Dutta, T. R.; Singh, R. P.; Gupta, S. D. (Indian Forester, 1982)
Field experiments were conducted at Jhansi in 1970-71 for the control of bush and broadleaf weeds in natural grasslands dominated by spear grass (H. contortus) , Picloram (Tordon 10 K pellets), 2, 4-D amine and atrazine with nitrogen application were tried. Tordon 10 K pellets @ 15-30 kg/ha applied as broadcast killed Z. nummularia. M, himalayana, L. camara, C. spinarum. S virosa and Z. xylopyrus in monsson season. The older and semiabsorbent plants of Z. nummularia. C. spinarum. S. virosa, Z. xrlopyrus escaped kill showing Merely defoliation with greater degree at higher dose. B. monosperma, A. leucophloea and F. indica did not respond to Picloram pellets. This herbicide also caused excellent control of existing broadleaf weeds. On the basis of pooled data of two yeara Trial. Tordon 10K pellets at 30 kg/ha appeared slightly more efficient over 15 kg which promoted grass yield by 59%. Top dressing of 50 kg N/ha as calcium-ammonium-nitrate (pellets) significantly ecvalted grass production over no nitrogen and saved application cost of Tordon in combined application.